The importance of the first generic substitution: Evidence from Sweden - Aljoscha Janssen; David Granlund (Research Institute of Industrial Economics (IFN), 2022)
We analyze changes in the willingness to substitute from prescribed pharmaceuticals to more affordable generic equivalents in response to the first experience with a substitution. Using Swedish individual-level data of prescribed and dispensed pharmaceuticals, we employ a dynamic event study and an instrumental variable approach to show that an initial substitution reduces the probability of opposing subsequent substitutions by 39 percentage points. The impact of a first substitution is especially large among elderly patients. We recommend that policy-makers target patients with a history of opposed substitution and offer additional discounts to promote substitution as long-term savings outweigh one-time costs.
Keywords: D12; I11; I12; 330; Generic Substitution; Pharmaceuticals; Health Care Costs